Sudies on the size distribution of the suspended dust particles in the atmosphere of Qena, Egypt (MAUSAM, 1989)
Studies on particular size, shape and distribution for the dust particles suspended In !he atmosphere of Qena (upper Egypt) have been carried out. The results show that the concentration of these particles decreases with Increasing Size according to lunge power law size distribution n (dp) = In 10 C ( dp )--(a+1). The values of exponent a range from 1.3 to 2. The largest number of particles have sizes less than 2 pm with irregular shape. Effective mean diameters were calculated.